2022
DOI: 10.1002/oby.23601
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of lipectomy and of adipose tissue transplantation

Abstract: Objective: The goal of this study was to review the metabolic effects of fat transplantation.Methods: Fat (adipose tissue [AT]) transplantation has been performed extensively for many years in the cosmetic reconstruction industry. However, not all fats are equal. White, brown, and beige AT differ in energy storage and use. Brown and beige AT consume glucose and lipids for thermogenesis and, theoretically, may provide greater metabolic benefit in transplantation. Here, the authors review the metabolic effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“… 30 , 31 However, transplantation of visceral WAT has produced deleterious effects, 15 , 32 while BAT transplantation has produced variable results, albeit mostly favorable. 33 Given its strong physiological influence and ease of translation to the clinic, we chose subcutaneous iWAT as the donor tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 However, transplantation of visceral WAT has produced deleterious effects, 15 , 32 while BAT transplantation has produced variable results, albeit mostly favorable. 33 Given its strong physiological influence and ease of translation to the clinic, we chose subcutaneous iWAT as the donor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 20 individuals with CGL2 revealed reduced lifespan by more than 30 years, with infectious disease listed as the cause of death in one‐third of individuals 21 . Additionally, although fat transplantation has been extensively performed for reconstructive and cosmetic surgery, a recent review of the literature by Davis and colleagues identified no studies reporting on the metabolic outcomes of human‐to‐human adipose tissue transplants 22 . Side effects of transplant can also include significant bleeding, infection, graft reabsorption/loss, peritonitis, bowel adhesions and fat embolism 22 …”
Section: Therapeutic Strategies To Restore Adipose Tissue Functionalitymentioning
confidence: 99%
“…21 Additionally, although fat transplantation has been extensively performed for reconstructive and cosmetic surgery, a recent review of the literature by Davis and colleagues identified no studies reporting on the metabolic outcomes of human-to-human adipose tissue transplants. 22 Side effects of transplant can also include significant bleeding, infection, graft reabsorption/loss, peritonitis, bowel adhesions and fat embolism. 22 Additionally, further elegant transplantation studies in lipodystrophic A-ZIP/F-1 transgenic mice raised the question as to whether adipose restoration was even strictly required to improve metabolic health in lipodystrophy.…”
Section: Adipose Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to distinguish between subcutaneous and visceral adipose tissue actions. These tissues differ in their expression patterns of different factors, with partial or total removal of visceral fat being shown to improve insulin sensitivity in rodents [ 2 ], whereas transplantation of subcutaneous fat is reported to generate positive effects on metabolic processes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%